Implementasi Enterprise Resource Planning Berbasis Web Menggunakan Framework Laravel - Devi Febriyanti Widia Astuti; Kurniawan; Bangkit; Fitri Yanti (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
This research focuses on developing an ERP application accessible through a web platform by utilizing the Laravel framework to support operational data integration within the company. The application development process adopted the Waterfall approach, which was carried out through several sequential stages including requirements identification, system design, implementation, evaluation, and maintenance. Laravel was used as the development framework and MySQL as the database management system. The findings indicate that the developed application is capable of consolidating operational information into a unified platform that can be accessed by different organizational units.